Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Bermain Platisin Pada Anak Usia 4-5 Tahun - Hamzanwadi; Wafda Firyal (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2025)
This study intends to encourage children's fine motor skills by using the method of playing plasticine in children of TKIT Anak Sholeh Praya in research is classroom action research (PTK) as for the subjects that have been studied are: students of study group Class A which amounted to 27 students 14 female 13 male students at TK IT Anak Sholeh Praya. This research uses methods that are applied in obtaining and processing data using work, observation and documentation.  The research that the researcher agendized was in the process of two cycles each carried out simultaneously 1 meeting. Procedural in this research there are 4 stages, namely planning (planning, implementation of action (action), observation (observation) and thinking, self-image (reflection.) In this classroom action research PTK used data collection, namely qualitative data. Through research shows that there is a significant increase in children's fine motor skills through plasticine play activities. From each phase of the cycle treatment, children's fine motor skills have increased from pre-cycle I to cycle II. In the research conducted, there is a significant development of children's abilities, this can be seen from the results of the percentage before and after playing plasticine, which reached 57% in cycle 1 and children were able to do it. Well so that it reaches 76% in cycle II. This shows an increase in children's fine motor skills through plasticine play activities Developing very well (BSB), So the essence of this research is an agenda program or shaping activities using plasticine can improve fine motor skills in class A aged 4-5 years at TKIT Anak Sholeh Praya.